INTRODUCTION OF ARTIFICIAL INTELLIGENCE INTO ECONOMICS AND FINANCE, PRACTICE OF USE IN THE MODERN WORLD - Makhmudjan Mukhamedjanovich Ikramov (Web of Journals Publishing, 2023)
In the article, the author outlines the degree of influence of artificial intelligence on the economy and business, and also examines its opportunities and problems.
Keywords: artificial intelligence, algorithm, data, machine learning, transaction, digital economy.